Captives of war British prisoners of war in Europe in the Second World War - Makepeace, Claire (Cambridge University Press, 2017)
"Signalman Andrew Makepeace, my grandfather, was taken prisoner, along with more than 10,000 other men in the 51st Highland Division, at St Valery-en-Caux on 12 June 1940. It was often said in our household that a veteran's silence on the war was a direct reflection of how much he had suffered. My parents regularly invoked this maxim to explain why my grandfather rarely talked about his experiences. From a very early age, I struggled to reconcile this: how could my kind, gentle, patient grandfather have gone through things so dreadful they had rendered him mute when it came to discussing these five years of his early adult life? Very occasionally, and unexpectedly, something would break his silence. I remember wearing a pair of clogs one day: I was about twelve years-old. He looked at them and then looked at me. 'Dreadful things' he said in a distant voice. I watched his eyes fill with anguish over, what seemed to me, up until that point, to be the most harmless of items."--Provided by publisher